Studi Kemampuan Tumbuh Anakan Mangrove Jenis Rhizophora mucronata, Bruguiera gimnorrhiza, dan Avicennia Marina Pada Berbagai Tingkat Salinitas - Eben Ezer Hutahaean; Cecep Kusmana; Helmy Ratna Dewi (Jurnal Manajemen Hutan Tropika, 1999)
Salinity is one of environmental factors having an important role in controlling mangrove growth. Our research results show that the degree of salinity has significant effect on the height seedling growth of Rhizophora mucronata, Bruguiera gimnorrhiza and Avicennia marina. Its salinity has also significant effect on the leaf growth of two later species. In general, the highest growth of both seedling’s height and the number of leaf for all species occur on the salinity ranged from 0.0 to 7.5 ppt.